Clinical Pharmacy Education in Japan: Using Simulated Patients in Laboratory-Based Communication-Skills Training before Clinical Practice - Kubota, Rie (Pharmacy (Basel), 2018)
The Japanese pharmaceutical curriculum was extended from four to six years in 2006. Students now receive practical communication-skills training in their fourth year, before progressing to train in hospital and community pharmacies in their fifth year. Kitasato University School of Pharmacy, Tokyo, had established a program to meet these aims before the 2006 guidance. In the present study, we discuss and evaluate the features of this communication-skills training program. This study enrolled 242 fourth-year pharmacy students at Kitasato University. Students filled out a questionnaire survey after completing the laboratory element of their undergraduate education. As part of training, students were asked to obtain patient data from a model medical chart, before performing simulated patient interviews covering hospital admission and patient counseling. These simulations were repeated in a small group, and feedback was provided to students by both the simulated patient and the faculty after each presentation. It was found that students were able to develop their communication skills through this approach. Thus, an effective system of gradual and continuous training has been developed, which allows students to acquire clinical and practical communication skills.